Long Non-coding RNA H19 Suppression Protects the Endothelium Against Hyperglycemic-Induced Inflammation via Inhibiting Expression of miR-29b Target Gene Vascular Endothelial Growth Factor a Through Activation of the Protein Kinase B/Endothelial Nitric Oxide Synthase Pathway - Cheng, Xiao-wen; Chen, Zhen-fei; Wan, Yu-feng; Zhou, Qing; Wang, Hua; Zhu, Hua-qing (Frontiers in Cell and Developmental Biology, 2019)
It has been shown that non-coding RNAs (ncRNAs) play an important regulatory role in pathophysiological processes involving inflammation. The vascular endothelial growth factor A (VEGFA) gene also participates in the inflammatory process. However, the relationships between ncRNAs and VEGFA are currently unclear. Here, this study was designed to determine the relationship between long non-coding RNA (lncRNA) H19, mircoRNA29b (miR-29b), and VEGFA in the development of diabetes mellitus (DM). We demonstrate that H19 is upregulated and miR-29b downregulated in individuals with DM and directly binds miR-29b. VEGFA is the target of miR-29b in the vascular endothelium of individuals with DM. We found that positive modulation of miR29b and inhibition of H19 and VEGFA significantly attenuates high glucose-induced endothelial inflammation and oxidative stress. We also found that the protein kinase B/endothelial nitric oxide synthase (AKT/eNOS) signal pathway in endothelial cells is activated through regulation of miR29b and H19 endogenous RNAs. We conclude that H19 suppression protects the endothelium against high glucose-induced inflammation and oxidative stress in endothelial cells by upregulation of miR-29b and downregulation of VEGFA through AKT/eNOS signal pathway activation. These results suggest a novel link between dysregulated ncRNA expression, inflammation, and the signaling pathway in the vascular endothelium of individuals with DM, indicating a promising strategy for preventing cardiovascular disease in such individuals.